European Small Business Finance Outlook 2021 - Helmut Kraemer-Eis; Antonia Botsari; Salome Gvetadze; Frank Lang; Wouter Torfs (European Investment Fund (EIF), 2021)
This working paper provides you with an overview of the main markets relevant to the EIF. It starts by discussing the general market environment, then looks at the markets for SME equity and debt products. In addition, it focusses on a number of thematic policy areas of interest to the EIF, such as Inclusive Finance, Fintech and Green finance & investment.
Keywords: 330